Legality of TikTok Shop Live Shopping Contracts: Building Three Pillars in Customer Protection - Muhammad Miqdam Makfi; Fajrul Mumtaz Kurniawan (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2026)
TikTok Shop live shopping has become a significant form of social commerce in Indonesia’s digital economy, yet its real-time, verbal, and platform-mediated transactions raise unresolved questions about contract validity and consumer protection. This article examines whether live shopping contracts satisfy the requirements of fiqh muamalah and whether Law No. 8 of 1999 on Consumer Protection adequately protects consumers in livestreaming transactions. Using normative legal research with statutory, conceptual, and comparative approaches, the article analyses Islamic legal texts, DSN-MUI fatwas, Indonesian legislation, and recent scholarship through a deductive-interpretive method. The findings show that live shopping contracts are valid in principle when ijāb-qabūl is clearly represented through the digital system, the contractual object is sufficiently identified, and gharar or tadlīs is absent. However, the Consumer Protection Act remains limited because it lacks livestreaming-compatible documentation, clear accountability for affiliates and influencers, and effective digital dispute resolution. The article proposes a three-pillar harmonization model: digital bayān standards, reconstructed accountability among platform actors, and ṣulḥ-based digital mediation. This model operationalizes ḥifẓ al-māl within Indonesia’s consumer protection framework. Live shopping TikTok Shop telah menjadi bentuk penting social commerce dalam ekonomi digital Indonesia. Karakter transaksinya yang berlangsung real-time, verbal, dan dimediasi platform menimbulkan persoalan tentang keabsahan akad serta perlindungan konsumen. Artikel ini menganalisis apakah akad live shopping memenuhi prinsip fikih muamalah dan apakah Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen memadai untuk melindungi konsumen dalam transaksi siaran langsung. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif. Bahan hukum berupa nash hukum Islam, fatwa DSN-MUI, peraturan perundang-undangan, dan literatur mutakhir dianalisis secara deduktif-interpretatif. Hasil penelitian menunjukkan bahwa akad live shopping pada prinsipnya sah apabila ijāb-qabūl terwakili secara jelas dalam sistem digital, objek akad dapat diidentifikasi, serta tidak mengandung gharar atau tadlīs. Namun, UU Perlindungan Konsumen masih memiliki keterbatasan karena belum menyediakan mekanisme dokumentasi siaran langsung, akuntabilitas yang jelas bagi afiliasi dan influencer, serta penyelesaian sengketa digital yang efektif. Artikel ini menawarkan model harmonisasi tiga pilar, yaitu standar bayān digital, rekonstruksi rantai akuntabilitas pelaku usaha, dan mediasi digital berbasis ṣulḥ untuk mengoperasionalkan prinsip ḥifẓ al-māl.